Kepentingan Nasional Suriah Dalam Upaya Penyelesaian Konflik Bersenjata di Idlib, Suriah dari tahun 2016-2017 - Abadi, Fany Anggun; Muhammad, Ali; Mukti, Takdir Ali (Indonesia Center for Middle East Studies, 2022)
Abstract The fighting in Idlib in 2016-2017 under bashar Al-Assad's rule and how it affected Syria's national interests. The civil conflict in Syria resulting from the Arab spring is almost entering its 10th year, leaving Idlib as the last door bar. The involvement of foreign actors gives an indication of the complexity of the conflict in Syria. the author gets a formulation of the problem in the form of: National Interest in Efforts to Resolve Armed Conflict in Idlib, Syria from 2016-2017. The purpose of this study is to find out the relevance of the fighting in Idlib to Syria's national security. This research was conducted using a qualitative method using a descriptive analysis approach and secondary data collection techniques obtained through literature studies in this case sourced from books, as well as journal articles. Furthermore, the concept of national interest is positioned as an analytical tool in the battle of Idlib, where one of the aspects contained in it is about national security. Based on the analysis using this concept, researchers found that the fighting that took place in Idlib would largely determine the continuity of the Syrian conflict, especially in the field of the country's national security. Keywords : Idlib, UN Security Council, Armed Conflict